Violence through information and communication technologies in secondary students - Álvarez García, David; Núñez Pérez, José Carlos; Álvarez Pérez, Luis; Dobarro González, Alejandro; Rodríguez Pérez, Celestino; González Castro, Paloma (Anales de Psicología / Annals of Psychology, 2010)
The aim of this paper was to analyze violence through Informa- tion and Communication Technologies (ICT) in Compulsory Secondary Education students. To achieve this objective, the School Violence Question- naire-Revised was applied to 638 Compulsory Secondary Education stu- dents, from six high schools in Asturias (Spain). Results show that vio- lence through ICT occurs with a remarkable frequency, although less than some kinds of traditional school violence. Statistically significative differ- ences were found among grades of Compulsory Secondary Education and between rural and urban centers. Violence through ICT is more frequent in second grade and in urban high schools. However, statistically significa- tive differences were barely found between genders. Also, a strong correla- tion between violence through ICT and some kinds of traditional school violence was found. These outcomes are compared with the results of the main previous works about this subject. Some educative implications of these results are discussed.